1060 Upper Tract Urothelial Carcinoma (UTUC) – What Can We Learn from Historical Cases. (12th October 2021) - Nandra, N; Rajan, K; KandaSwamy, G; Jefferies, M
Abstract: Background: UTUC has a poor prognosis with many patients presenting late, often without cardinal symptoms such as visible haematuria. Aims of this study were to assess presenting features, diagnostic tests and outcomes of patients with UTUC. Method: Retrospective data collection was performed for patients diagnosed with UTUC (ureteric /renal) between Jan 2013-Dec 2017. Data was collected on demographics, presenting features, diagnostic tests, presence of concurrent bladder UC and outcome/survival. Results: 67 patients were diagnosed with UTUC, 37 renal pelvis and 30 ureteric. The median age was 74 years (Range 49-90 years), M:F-2:1. 39 (58.2%) presented with haematuria, 1 having non-visible. 9 (13.4%) had loin pain, 4 (6.0%) systemic features (weight loss/lethargy), 15 (22.4%) other (detected on surveillance imaging, renal impairment). 61 had an USS of which 12 (19.7%) were normal and 49 demonstrated hydronephrosis or mass (80.3%). 21 (31.3%) had concurrent bladder UC. 9 (13.4%) prior to UTUC diagnosis (2 post cystectomy and 7 prior superficial UC) and 12 post diagnosis. 50 (74.6%) of UTUC were treated curatively with surgery and 17 (25.4%) palliated. The 2- and 5-year survival for those treated with curative intent was 79.9% and 58.5% compared to 31.25 and 7.5% for those treated with palliative intent. Conclusions: Most patients with UTUC presented with visible hematuria, pain, or systemic features. USS has a high sensitivity, but cases will still be missed. The presence of prior bladder cancer is a significant risk factor and regular upper tract monitoring should be performed in high-risk patients (post-cystectomy, high-risk non muscle-invasive UC).